Pembuatan Game RPG Edukasi “Aeary” Untuk Siswa Kelas III SMP - Denis Kusbowo; Rendi Kristyadi; Viny Christanti Mawardi (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
“Aeary” is an Role Playing Game with Education inside as its genre. This game created with Unity Game Engine. This game has for main characters where they are in charge of saving their city from enemy attacks by answering questions given by the enemy and divided into three arenas. In the arena one, player will answer questions about mathematics. In arena two player will answer questions about science. In arena three player will answer questions about mathematics and science. This game has a goal for students in preparation for the national exam and will be deployed on Android Based Smartphone with two dimensional view.